FAKTOR YANG MEMENGARUHI KEPUASAN PASIEN RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH Dr. ZUBIR MAHMUD KABUPATEN ACEH TIMUR TAHUN 2017 - Marmeam S.Kep; Tri Niswati Utami; Asiah Simanjorang (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
ABSTRACT Patient satisfaction is the response shown by the patient by comparing the perceived performance with expectations. If the results are felt below expectation, the patient will be disappointed, dissatisfied and even dissatisfied, but otherwise if it is in accordance with expectations, the patient will be satisfied and if the performance exceeds expectations, the patient will be very satisfied. Methods: This research used analytic survey method with cross sectional survey design. The population in this study were all outpatients who visited Dr. Zubir Mahmud Hospital East Aceh Regency in September 2017 as many as 3900 people with a sample of 100 respondents. Results: The results of bivariate test showed that there is a relationship of physical evidence (tangible). reliability, responsiveness and assurance of Patient Satisfaction. Multivariate test was found to have effect of physical evidence (tangible) p = 0.021, reliability p = 0.025, and responsiveness p = 0.023 with significance value <0,005 and unrelated variable is assurance service variable and empathy (emphaty). Conclusion: The most influential variable is physical evidence (tangible). Reliability (reliability), responsiveness (responsiveness). Suggestions for the people who seek outpatient and inpatient care will cooperate to maintain the facilities and infrastructure facilities in hospitals Dr. Zubir Mahmud, and follow the rules for patients who have been set up the dr. Zubir Mahmud. Keywords: Patient Satisfaction, Tangible, Reliability, Responsiveness, Assurance, Emphaty